Niveles y predominio de estereotipación de género en la esfera académica y personal social de estudiantes, carrera de educación secundaria - Chávez Bosas, Teresa Jesús (2019)
ABSTRACT This research aims to identify what levels and prevalence of gender stereotypes in the Academic Personal Social Spheres in freshmen of Secondary Education Career of the National University of Trujillo in 2014. The population was 190 students and the sample was 166 students who were administered measuring instruments. To measure the degree of stereotyping students inventory Towards Gender stereotyping (IEHG) was used. It was based on the Likert scale and the scale of skills to women, Spencer and Helmrider. This inventory consists of 42 items divided into two areas: Academic and Personal-Social which has five lies by area as a criterion for selection of the sample. As the overall level of stereotyping 78% of male students of the first year of secondary school career reach high levels of stereotyping, and 62.1% of female students achieve a high level estereotipación..A spheres of freshmen career Secondary Education are highly stereotyped in the Personal Social sphere, while in the academic sphere are at a low level of stereotyping, plus a predominance of female stereotypes found in students women, while male students presented to the opposite gender stereotypes and more predominant to their own gender. It was concluded that males are placed in a higher level of stereotype that women and gender stereotypes most prevalent correspond to the female of emotional expression, fragility and delicacy than male stereotypes of aggressiveness